Estratégias de resolução dos conflitos conjugais: uma explicação a partir da personalidade e dos valores humanos - Freitas, Nájila Bianca Campos (2017)
The present dissertation aims to analyze if personality traits and human values predict strategies for solving marital conflicts. Specifically, we sought to verify the influence of sociodemographic variables on strategies for resolving marital conflicts; to identify the relation between the personality traits, the value subfunctions and the strategies of resolution of the marital conflicts; In addition to knowing the extent to which personality traits and human values explain conflict resolution strategies. A total of 252 married people from the city of Joao Pessoa (PB), 57.1% female, with an average age of 38 years (SD = 10.87), officially married (68.9%), union time greater than 10 years (51.0%). They answered the Conflict Resolution Behavior Questionnaire, the Basic Values Questionnaire, the Inventory of the Five Great Personality Factors, and a sociodemographic questionnaire. The SPSS program was used to perform the descriptive analyzes, the MANOVA's, the correlations (Pearson r) and the Multiple Linear Regressions (stepwise method). The results showed that the strategies for resolving marital conflicts were statistically significant for the gender variables [λ = .94, F (3. 245) = 5.60, p < .001, η² = .06], with women scoring in attack [F (1. 249) = 4.90, p = .03] and the men in avoidance [F (1.249) = 5.13, p = .02; η² = 0.06] ; day of work / daily [λ = .94, F (3. 169) = 3.77, p = .01], the spouses who worked up to 8 hours scored more on avoidance [F (1.173) = 6.59, p = .01]; and, marital status [λ = .96, F (3. 245) = 3.47, p = .02, η² = .04], people living together (cohabitation) scored more in attack [F (1. 249) = 9.76, p = < .01), besides, negative and significant correlations were observed between professional service time and attack (r = -.17, p < .05) and Level of religiosity and avoidance (r = -.13, p = .03). About the correlations between the constructs, it was observed that in relation to the compromise strategy, it was positively and significantly correlated with personality traits openness to experience (r = .18, p < .01), conscientiousness (r = .20; p < .01), extroversion (r = .18, p < .01), agreeableness (r = .24; p < .01) and negatively with neuroticism (r = -.15; p < .05). The attack strategy correlated positively and significantly with neuroticism (r = .37, p < .01) and negative with agreeableness (r = -.22, p < .01). However, the avoidance strategy correlated negatively and significantly only with agreeableness (r = -.23, p <.01). Regarding the value sub-functions, there was a positive and significant correlation between compromise strategy and supra-personal (r = .18, p < .01) and interactive sub-functions (r = .13, p < .05 ). When performing the linear regressions, it was observed that the attack strategy was predicted by personality traits neuroticism (β = .35, p < .001) and agreeableness (β = -.19, p = .001); Since avoidance was predicted by the agreeableness trait (β = -.23, p < .001); And the compromise strategy was predicted by traits agreeableness (β = .19, p < .05), openness to experience (β = .14, p = .03) and neuroticism (β = -.15 , p = .01), in addition to supra-personal sub-function (β = .18, p = .004). Thus, it is concluded that personality traits and human values, as well as sociodemographic variables, influence the adoption of strategies for resolving marital conflicts. This fact suggests the application of these results in clinical contexts aimed at minimizing marital problems and offering a better marital quality.